2010
DOI: 10.1002/etc.384
|View full text |Cite
|
Sign up to set email alerts
|

Competitive stress can make the herbicide Roundup® more deadly to larval amphibians

Abstract: Toxicity assessments on nontarget organisms have largely been addressed using short-term, single-species laboratory experiments. Although extremely helpful, these experiments inherently lack many pervasive ecological stressors found in nature. Though a substantial challenge, incorporating these ecological stressors in contaminant studies would shed light on potential synergistic effects. For the world's leading herbicide, glyphosate, we know little about how natural stressors affect the toxicity to nontarget o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 41 publications
4
55
1
1
Order By: Relevance
“…Contemporary ecotoxicological studies focus more widely on how sublethal concentrations of contaminants interact with natural stressors, including inter-and intraspecific competition (e.g., Relyea et al 2005;Jones et al 2011), predation (Relyea and Edwards 2010;Todd et al 2011a), environmental stochasticity (e.g., Boone and Semlitsch 2002), and parasites (e.g., Budischak et al 2008), as well as environmentally realistic contaminant mixtures (e.g., Snodgrass et al 2004;Relyea 2009). These studies have revealed that environmental contaminants can have a wide array of adverse sublethal effects on larval amphibians (Rowe et al 2001;Budischak et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary ecotoxicological studies focus more widely on how sublethal concentrations of contaminants interact with natural stressors, including inter-and intraspecific competition (e.g., Relyea et al 2005;Jones et al 2011), predation (Relyea and Edwards 2010;Todd et al 2011a), environmental stochasticity (e.g., Boone and Semlitsch 2002), and parasites (e.g., Budischak et al 2008), as well as environmentally realistic contaminant mixtures (e.g., Snodgrass et al 2004;Relyea 2009). These studies have revealed that environmental contaminants can have a wide array of adverse sublethal effects on larval amphibians (Rowe et al 2001;Budischak et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In some Brazilian regions, this amount of contamination can be related to a pesticide and herbicide use that is up to 3.2 times higher than the global mean (Pignati & Machado, 2007). Thus, it is not unrealistic for tadpoles to be exposed to glyphosate contamination levels comparable to the concentrations used in our experiments and in toxicity bioassays conducted with amphibian eggs and tadpoles in the wild (e.g., Mann & Bidwell, 1999;Lajmanovich et al, 2003;Relyea, 2005b, c;Relyea & Jones, 2009;Jones et al, 2010Jones et al, , 2011Relyea, 2012;Simioni et al, 2013;Figueiredo & Rodrigues, 2014). The LC50 96h for P. cuvieri was 2.13 mg a.i./l, which is considered moderately toxic according to glyphosate toxicity classification on aquatic organisms (Giesy et al, 2000;U.S.EPA., 2008) and was lower than that recorded for other congeneric species (P. albonotatus, LC50 96h = 5.38 mg a.i./l, moderately toxic, Simioni et al, 2013; P. centralis, LC50 96h = 19.7 mg a.i./l, slightly toxic, Figueiredo & Rodrigues, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…Studies evaluating the herbicide Roundup (a.i. glyphosate) indeed indicated that increased natural competition (Jones et al 2011) and presence of predators (Relyea 2005) increased the toxicity of this test compound to L. catesbeianus tadpoles.…”
Section: Introductionmentioning
confidence: 86%